ANALYSIS OF THE DECISION OF THE LANGSA SYARIAH MAHKAMAH NO 355/Pdt.G/Ms.Lgs ON THE OWNERSHIP OF THE LEASING OBJECT BY THE LESSOR UNDER THE CONCEPT OF BA'I MURABAHAHAH - Muhammad Masykur (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2024)
This study analyzesthe decision of the Mahkamah Syariah Langsa No. 355/Pdt.G/Ms.Lgs regarding the repossession of leasing objects by the lessor in a bai’ murabahah contract. Sharia financing companies often utilize murabahah contracts in their operations, emphasizing transparency and fairness. However, this case highlights a violation of sharia principles due to the forced repossession of leasing objects without consultation or court orders. The study aims to evaluate the conformity of the lessor's actions with murabahah principles and Islamic economiclaw.This research employs a normative juridical approach with a descriptive-analytical method. Primary data is derived from the Mahkamah Syariah Langsa decision No. 355/Pdt.G/Ms.Lgs, while secondary data includes Islamic legal literature and relevant regulations. The analysis examines the pillars and conditions of murabahah contracts as well as the judges' considerations in theruling.The findingsrevealthatthe repossession of leasing objects was triggered by the debtor's default in installment payments. The lessor based their actions on a contractual clause granting full authority to execute the leased object. However, such actions contradict sharia principles, which require consultation or arbitration to resolve disputes. The court rejected the plaintiff's claim due to insufficient evidence of unlawful acts by the defendant. The repossession was deemed consistent with the agreement, despiteproceduralviolations.